Pengaruh Terapi Bermain Mewarnai terhadap Penurunan Kecemasan Anak Prasekolah yang Mengalami Hospitalisasi: Effectiveness of Coloring Play Therapy in Reducing Anxiety Among Hospitalized Preschool Children - Novia Pratiwi; Feri Catur Yuliani; Luluk Dermawan (Jurnal Keperawatan Berbudaya Sehat, 2026)
Hospitalization triggers psychological stress and anxiety in preschool children due to unfamiliar environments and medical procedures. This study aims to analyze the effect of coloring play therapy on reducing anxiety in hospitalized preschool children in the Multazam Ward of RSU Nurussyifa Kudus. This quantitative study utilized a pre-experimental approach with a one-group pretest-posttest design. A sample of 75 preschool children was selected using a purposive sampling technique. Anxiety levels were measured before and after the intervention using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of 5% ( ). The results showed that before the coloring play therapy, the majority of children (50.6%) experienced very severe anxiety. After the intervention, most children (40.0%) showed no anxiety. Statistical analysis obtained a p-value < 0.001. In conclusion, there is a significant effect of coloring play therapy on reducing anxiety levels in hospitalized preschool children.